Population Decline in Lithuania: Who Lives in Declining Regions and Who Leaves? - Rūta Ubarevičienė; Maarten van Ham (Institute for the Study of Labor (IZA), 2016)
Since the 1990s, Lithuania lost almost a quarter of its population, and some regions within the country lost more than 50% of their residents. Such a sharp population decline poses major challenges to politicians, policy makers and planners. This study aims to get more insight into the recent processes of socio-spatial change and the role of selective migration in Lithuania. The main focus is on understanding who lives in those regions which are rapidly losing population, and who is most likely to leave these regions. This is one of the first studies to use individual level Lithuanian census data from 2001 and 2011. We found that low socio-economic status residents and older residents dominate the population of shrinking regions, and unsurprisingly we found that the most "successful" people are the most likely to leave such regions. This process of selective migration reinforces the negative downward spiral of declining regions. As a result, socio-spatial polarisation is growing within the country, where people with higher socio-economic status are increasingly overrepresented in the largest city-regions, while the elderly and residents with a lower socioeconomic status are overrepresented in declining rural regions. This paper provides empirical evidence of selective migration and increasing regional disparities in Lithuania. While the socio-spatial changes are obvious in Lithuania, there is no clear strategy on how to cope with extreme population decline and increasing regional inequalities within the country.
Keywords: R23; O15; J11; P20; 330; population decline; shrinking regions; internal migration; socio-spatial polarisation; Lithuania